Social skills development, assessment and programming in school-aged speakers with autism spectrum disorders - Paul, Rhea (Henry Stewart Talks, 2010)
Typical development of social communication, Pragmatic development in school age, later childhood and adolescence, Differences in language development in ASD, Impairments in pragmatic skills, Assessment of pragmatic and social skills, Experimental investigations of pragmatic communication, Yale Pragmatic Rating Scale (YPRS), Critical observations for speakers with ASD, Evidence-based approaches to social skills programming, Principles of pragmatic intervention strategies
Archived at 2020/08/31